2020
DOI: 10.1155/2020/4056591
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Postoperative Health Status of Patients with Nonfunctioning and Secretory Pituitary Adenomas and an Analysis of Related Factors

Abstract: Purpose. To identify the characteristics of the physical and mental health status of patients with pituitary adenomas, explore the postoperative reversibility of impaired health status, and assess the impact of clinical characteristics, hormone levels, anxiety, depression, and disease stigma on health status. Methods. We prospectively enrolled 147 and 138 patients with nonfunctioning and secretory pituitary adenomas, respectively. Health status was evaluated in 8 domains using the 36-item Short-Form Health Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Increased duration of opioid use was also associated with a history of anxiety and depression. Compared with the healthy population, patients with pituitary adenomas have higher rates of anxiety and depression than the general population, and these illnesses persist even after surgical intervention 15,16 . Similarly, patients with other anterior skull base neoplasms, such as meningiomas and olfactory neuroblastoma, also have increased rates of comorbid anxiety and depression 17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased duration of opioid use was also associated with a history of anxiety and depression. Compared with the healthy population, patients with pituitary adenomas have higher rates of anxiety and depression than the general population, and these illnesses persist even after surgical intervention 15,16 . Similarly, patients with other anterior skull base neoplasms, such as meningiomas and olfactory neuroblastoma, also have increased rates of comorbid anxiety and depression 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the healthy population, patients with pituitary adenomas have higher rates of anxiety and depression than the general population, and these illnesses persist even after surgical intervention. 15,16 Similarly, patients with other anterior skull base neoplasms, such as meningiomas and olfactory neuroblastoma, also have increased rates of comorbid anxiety and depression. 17,18 This higher prevalence of anxiety and depression in the ESBS population may influence postoperative opioid use.…”
Section: F I G U R Ementioning
confidence: 99%
“…Numerous emotional issues, such as anxiety, depression, behavioral disorders, and personality changes, may be linked to pituitary illnesses [ 44 ]. A previous study reported that 11.6% of PA patients had anxiety, and 30.9% had depression [ 45 ]. A study from Canada found that almost 40% of participants had clinically significant symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…patients suffer from more general symptoms, such as headache, fatigue, anxiety, and depression [6,7]. The appearance of these symptoms may lead to the quality of life impaired [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The results emphasize the importance of fatigue and alcohol use in the sleep disturbance of PA patients. Medical personnel should pay more attention to PA patients with sleep disturbance before the initial diagnosis and preparation for surgery in order to take effective measures early to improve sleep disturbance, with the ultimate goal to improve their QoL.patients suffer from more general symptoms, such as headache, fatigue, anxiety, and depression [6,7]. The appearance of these symptoms may lead to the quality of life impaired [8,9].Sleep is one of the basic and indispensable activities of daily life that affect individual health and quality of life.…”
mentioning
confidence: 99%